Envy as a Criterion for Distributive Justice - Pereira, Gustavo (2001)
This paper is concerned with the search for a limiting criterion for the inequalities admitted in every distrtbution of resources. Taking as a standpoint Rawls' principie of difference, it will be suggested as limiting criterion of inequality the appearance of feelings of envy, due to the perception of great differences in the possession of resources. This criterion is founded in the problems of stability that envy generates, since people that envy someone's possession of goods will stop being fully cooperative agents, and both individual autonomy as well as social stability will be questioned.